2015
DOI: 10.1002/jwmg.924
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of resident Canada goose movements to reduce the risk of goose‐aircraft collisions at suburban airports

Abstract: Resident (non‐migratory) Canada goose (Branta canadensis) populations in suburban environments pose risks to human health and safety. Specifically, the relatively large size and gregarious behavior of geese combined with an overlap in aircraft flight space pose substantial risk of property damage and human fatalities from goose‐aircraft collisions. We estimated home range and core use areas of resident Canada geese and evaluated goose movements to better define the risk of goose‐aircraft collisions around Pied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
(10 reference statements)
0
4
1
Order By: Relevance
“…Our home range area estimates during winter and late winter are similar to those reported for Canada geese marked during winter in the greater Chicago metropolitan area ). However, our estimates of median home range were larger than mean home range estimates reported for Canada geese in suburban areas of North Carolina, although time periods during which home ranges were calculated differed (Rutledge et al 2015). During hunting seasons and excluding migratory movement, Canada geese are likely most mobile during autumn (September and October).…”
Section: Home Rangescontrasting
confidence: 73%
See 2 more Smart Citations
“…Our home range area estimates during winter and late winter are similar to those reported for Canada geese marked during winter in the greater Chicago metropolitan area ). However, our estimates of median home range were larger than mean home range estimates reported for Canada geese in suburban areas of North Carolina, although time periods during which home ranges were calculated differed (Rutledge et al 2015). During hunting seasons and excluding migratory movement, Canada geese are likely most mobile during autumn (September and October).…”
Section: Home Rangescontrasting
confidence: 73%
“…During hunting seasons and excluding migratory movement, Canada geese are likely most mobile during autumn (September and October). Decrease in home range areas from autumn to winter periods were also observed in Canada geese in suburban North Carolina (Rutledge et al 2015). While urban geese used smaller areas and were less likely to leave city limits during hunting seasons, individuals did leave city limits to forage in agricultural fields, while no individuals were observed doing so during winter in Chicago .…”
Section: Home Rangesmentioning
confidence: 66%
See 1 more Smart Citation
“…Reducing the number of aircraft collisions with animals is one of the main goals of airport wildlife management actions. In many studies, the number of collisions is used as a proxy for risk evaluation at airports (Krupka 2000, Zakrajsek and Bissonette 2005, Allan 2006, Rutledge et al 2015, Allan et al 2016). Due to its large size, weight, and abundance, current Brazilian laws classify burrowing owls as posing a relevant risk to aircraft (BRASIL 2015).…”
Section: Discussionmentioning
confidence: 99%
“…If lethal control is considered an option, the roundup of individuals must be extensive enough to impact the population in the vicinity of the airport. A study of neck-tagged Canada geese at Greensboro, North Carolina revealed that removing geese from a single site resulted in re-colonisation within only 27 days, underscoring the necessity of repeated removal of geese within an 8-km radius around an airport (Rutledge et al 2015 ). The use of hunting to disturb geese and potentially regulate the population can offer a form of cost-neutral management option.…”
Section: Managing Geese Offsitementioning
confidence: 99%